Comprehensibility of a personalized medication overview compared to usual-care prescription drug labels - Schackmann, Laura; van Dijk, Liset; Brabers, Anne E. M.; Zwier, Sandra; Koster, Ellen S.; Vervloet, Marcia (Frontiers in Pharmacology, 2022)
Poor understanding of prescription drug label (PDL) instructions can lead to medication errors, suboptimal treatment (side) effects, and non-adherence. A personalized medication hard-copy overview listing PDL instructions and visual information may support patients in their medication use. This study aimed to investigate the comprehensibility of PDL instructions on a personalized medication overview compared to usual-care PDL instructions presented on a medication box. A hypothetical-online-experiment was set up, comparing groups of respondents exposed vs. not exposed to the medication overview and who received PDL instructions for three, five, or eight medications. Participants were divided randomly in six groups. Online questionnaires were sent to a stratified sample of 900 members from the Nivel Dutch Healthcare Consumer Panel. Outcome measures included comprehension of instructions for medication use, e.g. how often, dose timing, usage advice and warnings for a medication with simple use instructions (omeprazol) and more complex use instructions (levodopa/carbidopa (L/C)). To analyze differences between experimental conditions ANOVA testing was used. 604 respondents (net response 67%) completed the questionnaires. Respondents exposed (E) to the overview gave a higher proportion of correct answers compared to non-exposed (NE) respondents for usage advice (L/C: mean 0.83, SD 0.4 E; 0.03, SD 0.2 NE, p<0.001; omeprazol: mean 0.85, SD 0.4 E; 0.10, SD 0.3 NE, p<0.001). Both groups gave the same proportion of correct answers (mean 0.80, SD 0.4, p=1.0) for dose timing of omeprazol. More NE respondents gave correct answers for how often (mean 0.85, SD 0.4 NE; mean 0.76, SD 0.4 E, p=0.02) and dose timing (mean 0.92, SD 0.3 NE; mean 0.86, SD 0.4 E, p=0.04) of L/C. No differences were found regarding number of medications nor were interaction effects found between the number of medications and information type. As a medication overview contains additional information, it can be a good addition in supporting patients in their medication use compared to usual-care PDLs. Future research should focus on identifying patient groups who might benefit more from a medication overview, by testing the effect of such overview on this group.